2014
DOI: 10.1002/ange.201406100
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine‐Catalyzed Annulations of 4,4‐Dicyano‐2‐Methylenebut‐3‐enoates with Maleimides and Maleic Anhydride

Abstract: A novel phosphine-catalyzed [4+1] annulation of maleimides with 4,4-dicyano-2-methylenebut-3-enoates has been developed to afford spirocyclic products, and the maleimides serves as C 1 synthons. Moreover, a phosphinecatalyzed formal [3+2] annulation between 4,4-dicyano-2methylenebut-3-enoates and maleic anhydride has been also achieved, and maleic anhydride behaved as a C 3 synthon in the reaction, thus efficiently affording the functionalized cyclopentenones. A stable phosphinium-containing zwitterionic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…It was not until 2014 that the Shi group disclosed the interesting reactivities of maleimides and maleic anhydrides behaving as one- and three-carbon synthons, respectively. 158 With maleimide and 1,3-butadiene as reaction partners, they synthesized a collection of functionalized spirocyclopentenes through a phosphine-catalyzed [4 + 1] annulation pathway (Scheme 86). Starting from the 1,3-butadiene, the zwitterion 48 is formed readily in the presence of triphenylphosphine.…”
Section: Nucleophilic Phosphine Catalysis Of Alkenesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not until 2014 that the Shi group disclosed the interesting reactivities of maleimides and maleic anhydrides behaving as one- and three-carbon synthons, respectively. 158 With maleimide and 1,3-butadiene as reaction partners, they synthesized a collection of functionalized spirocyclopentenes through a phosphine-catalyzed [4 + 1] annulation pathway (Scheme 86). Starting from the 1,3-butadiene, the zwitterion 48 is formed readily in the presence of triphenylphosphine.…”
Section: Nucleophilic Phosphine Catalysis Of Alkenesmentioning
confidence: 99%
“…In addition to the [4 + 1] annulation pathway, an unusual [3 + 2] annulation was also disclosed in the same Communication. 158 Through this pathway, maleic anhydride reacted to provide a three-carbon synthon for the annulation (Scheme 88). The initially formed zwitterion 51 undergoes addition to maleic anhydride to generate the intermediate 52 .…”
Section: Nucleophilic Phosphine Catalysis Of Alkenesmentioning
confidence: 99%
“…In addition to the MBH carbonates, Shi’s group recently revealed that maleimides 315 can serve as the C1 synthon to undergo an interesting formal [4+1] annulation with 4,4-dicyano-2-methylenebut-3-enoates 314 by nucleophilic phosphine catalysis (Scheme ) . Using 10 mol % of PPh 3 as the organocatalyst in toluene at 60 °C, the reaction with various aryl and heteroaryl-substituted 4,4-dicyano-2-methylenebut-3-enoates 314 and aryl or alkyl-bearing maleimides 315 smoothly proceeded to furnish the corresponding highly functionalized spirocyclic compounds 316 in generally acceptable yields.…”
Section: Ylides-based Formal [4+1] Annulationmentioning
confidence: 99%
“…214 In addition to the MBH carbonates, Shi's group recently revealed that maleimides 315 can serve as the C1 synthon to undergo an interesting formal [4+1] annulation with 4,4dicyano-2-methylenebut-3-enoates 314 by nucleophilic phosphine catalysis (Scheme 114). 215 Using 10 mol % of PPh 3 as the organocatalyst in toluene at 60 °C, the reaction with various aryl and heteroaryl-substituted 4,4-dicyano-2-methylenebut-3enoates 314 and aryl or alkyl-bearing maleimides 315 smoothly proceeded to furnish the corresponding highly functionalized spirocyclic compounds 316 in generally acceptable yields. The deuterium-labeling experiments and successful isolation of the stable zwitterions 314A and 314A′ (R 1 = 4-MeC 6 H 4 , R 2 = Me), which were initially formed from tertiary phosphine and 314, implied that these species are possible intermediates for this [4+1] annulation.…”
Section: With Aldehydes Ketones and Estersmentioning
confidence: 99%